Efeito do agente precursor na transparência de filmes nanoestruturados de NiO - Lima, Paulo Vitor Silva de (2015)
In this work, nickel oxide films were prepared from the Spray Pyrolysis Technique, due to its wide application in the manufacture of various electronic devices and intense study of its semiconducting properties. The films were obtained from a precursor solution containing 0.2 mol / L NiCl2 dissolved in distilled water containing sucrose as a chelating agent, deposited on a glass substrate temperature of 450 ° C. The sucrose concentration in the solution ranged from 0 to 10 × 10-3 mol/L and its effects on structural, morphological and optical properties were studied using the techniques of X-ray diffraction, scanning electron microscopy and UV-vis spectroscopy. It was observed that, before the concentration of sucrose, the films have different optical characteristics (transparent or opaque) for amorphous or crystalline films.